Climate change scenarios in Malaysia: engaging the public - Abdul Rahman, Haliza (Faculty of Cultural Sciences-Hasanuddin University, 2018)
Introduction: Climate change are any change of climate that is attributed directly or indirectly to human activity that alters the composition of the global atmosphere and that is in addition to natural climate variability observed over comparable periods. Climate change has become a global environmental issue which dominates the international agenda and one of the most issues for mankind.Research methodology: This paper involved with secondary data which are collected from journal, proceedings, books and internet sources regarding the topic. Result and discussion: Malaysia could be considered as a free zone from climate related disaster. However, mild climate related disasters are quite frequent to happen lately. The potential impacts of climate change in the Malaysian context would include sea level rise, reduced crop yields, greater diseases among forest species and biodiversity loss, erosion of shorelines, increased flood intensities, coral reef bleaching, increased incidences of disease, tidal inundation of coastal areas, decreased water availability, loss of biodiversity, and more droughts. To tackle the scenarios, Malaysia adopts ‘precautionary principles’ to mitigate and adapt to climate change. However, the important and immediate action needed in mitigating the climate change effects is the actively participating and involving the public in this issue.Conclusion: Malaysia has made significant progress in setting up legal framework for the implementation of climate change mitigation and voluntary environmental disclosure. Improving education, training and public awareness on climate change is an important measure for persuading the whole of society to jointly participate in activities for the mitigation of an adaptation to climate change.